IMF Survey : Volume 29, Issue 03. (IMF Survey; IMF Survey, 2000)
Speaking before the Council on Foreign Relations in New York on February 1, IMF Managing Director Michel Camdessus addressed the role of the IMF at the start ofa new century. In his remarks, Camdessus emphasized the institution's ability to adapt to the challenges of a continually evolving global economy-in its response to both the needs of its members and the systemic needs of the global economy. He stressed that the IMF's responsibilities to its members extended beyond crisis prevention- that is, its surveillance function-to include poverty reduction and crisis management. On the global front, Camdessus said, calls for reform of the international financial architecture implied greater economic policy coordination and cooperation among all nations and with international institutions to maintain global stability and reduce the incidence and severity of financial crises. Following are edited excerpts of Camdessus's remarks. The full text is available on the IMF's website (www.imf.org).